Molecular characterization, DNA fingerprinting and genetic diversity analysis of Nepalese rice landraces using SSR markers - Bal Krishna Joshi; Nancy Shrestha; Rakshya Pokhrel; Raju Chaudhary (Nepal Journal of Biotechnology)
Rice (Oryza sativa) is the major crop of Nepal. Genetic diversity studies in rice have been conducted extensively with collections from various parts of the world, including Nepal. However, local landraces in these collections are explored on a very limited scale for novel genetic variations. The availability of wild relatives of Oryza sativa has increased interest in understanding the genetic makeup of Nepalese rice landraces. This study aimed to identify the variability in 80 rice landraces using 19 simple sequence repeat (SSR) markers. The collection represented geographical regions suitable for rice farming in Nepal. DNA fingerprints of some landraces showed clear distinctions. The results indicated significant genetic differentiation among the rice landraces, with a possible formation of two distinct clusters. Among 19 SSR markers, only 12 have shown polymorphism. The lowest allele frequency was observed in the Tauli Satara landrace. The maximum heterozygosity was observed from the sample collected from Pyuthan district. The first coordinate explained 18.81% of the variation, while the second coordinate explained 13.16%. Overall, these findings will benefit rice breeders and conservationists in selecting parent material, managing conservation efforts both on-farm and ex-situ, and linking genetic diversity with geographical locations.